(untitled) (Journal of Bangladesh Academy of Sciences, 2011)
The physical and mechanical properties of hybrid Acacia, produced from natural crossing between two introduced timber species (Acacia auriculiformis and Acacia mangium) were studied. The timber hybrid Acacia is of medium dense having specific gravity 0.56 at green condition which is less than that of teak (Tectona grandis). The volumetric shrinkage of hybrid Acacia wood was found greater than that of teak but the specific gravity was found less than that of teak. From the study of physical and mechanical properties it is evident that the species is moderately strong. The species is suitable for making furniture and other household articles. Key words: Hybrid Acacia; Specific gravity; Physical properties; Mechanical properties DOI: 10.3329/jbas.v34i2.6864 Journal of Bangladesh Academy of Sciences, Vol. 34, No. 2, 181-187, 2010